2022
DOI: 10.3390/genes13071225
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antitumor miR-30e-5p Controlled Genes; Diagnostic and Prognostic Biomarkers for Head and Neck Squamous Cell Carcinoma

Abstract: Analysis of microRNA (miRNA) expression signatures in head and neck squamous cell carcinoma (HNSCC) has revealed that the miR-30 family is frequently downregulated in cancer tissues. The Cancer Genome Atlas (TCGA) database confirms that all members of the miR-30 family (except miR-30c-5p) are downregulated in HNSCC tissues. Moreover, low expression of miR-30e-5p and miR-30c-1-3p significantly predicts shorter survival of HNSCC patients (p = 0.0081 and p = 0.0224, respectively). In this study, we focused on miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, the passenger strands of miR-30a and miR-30e still remain poorly studied in HNSCC. Using TCGA-HNSC data, Minemura and colleagues confirmed that miR-30a-3p and miR-30e-3p were downregulated in HNSCC [ 12 ]. Patients with low expression of miR-30e-3p had significantly poorer prognosis compared to those with a high expression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the passenger strands of miR-30a and miR-30e still remain poorly studied in HNSCC. Using TCGA-HNSC data, Minemura and colleagues confirmed that miR-30a-3p and miR-30e-3p were downregulated in HNSCC [ 12 ]. Patients with low expression of miR-30e-3p had significantly poorer prognosis compared to those with a high expression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, several studies have shown that dysregulation of miRNAs can profoundly impact normal physiology and enhance oncogenesis [ 10 , 11 ]. Analysis of miRNA signature and TCGA has revealed that the miR-30 family is frequently downregulated in HNSCC [ 12 , 13 ]. The miR-30 family contains six miRNAs (miR-30a/b/c1/c2/d/e) encoded by six genes located on three distinct loci of the human genome (chromosome 1 for miR-30e/c1, chromosome 6 for miR-30a/c2, and chromosome 8 for miR-30d/b) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The assay for RIP was performed according to previous studies [ 55 ]. Briefly, CRC cells were cultured in 6-well dish at 3.0 × 10 5 /well concentration.…”
Section: Methodsmentioning
confidence: 99%